Clinical, Immunological, and Molecular Findings in Four Cases of B Cell Expansion With NF-κB and T Cell Anergy Disease for the First Time From India - Gupta, Maya; Aluri, Jahnavi; Desai, Mukesh; Lokeshwar, Madhukar; Taur, Prasad; Lenardo, Michael; Bergerson, Jenna; Dalvi, Aparna; Mhatre, Snehal; Kulkarni, Manasi; Kambli, Priyanka; Madkaikar, Manisha (Frontiers in Immunology, 2018)
B cell Expansion with NF-κB and T cell Anergy (BENTA) is a rare primary immunodeficiency disorder caused by mutations in the CARD11 gene and results in constitutive NF-κB activation in B and T cells. Affected patients present with the polyclonal expansion of B cells at an early age with splenomegaly, lymphadenopathy and mild autoimmunity. Here, we discuss four BENTA cases with unusual clinical manifestations not previously reported. All patients showed previously reported gain of function mutations (G123S, G123D, and C49Y) in the CARD11 gene. Severe autoimmune manifestations were noted for the first time in all our patients.